In vitroandin vivostudy of hazardous effects of Ag nanoparticles and Arginine-treated multi walled carbon nanotubes on blood cells: Application in hemodialysis membranes - Zare-Zardini, H.; Amiri, A.; Shanbedi, M.; Taheri-Kafrani, A.; Kazi, S.N.; Chew, B.T.; Razmjou, A. (John Wiley & Sons, 2015)
One of the novel applications of the nanostructures is the modification and development of membranes for hemocompatibility of hemodialysis. The toxicity and hemocompatibility of Ag nanoparticles and arginine-treated multiwalled carbon nanotubes (MWNT-Arg) and possibility of their application in membrane technology are investigated here. MWNT-Arg is prepared by amidation reactions, followed by characterization by FTIR spectroscopy, Raman spectroscopy, and thermogravimetric analysis. The results showed a good hemocompatibility and the hemolytic rates in the presence of both MWNT-Arg and Ag nanoparticles. The hemolytic rate of Ag nanoparticles was lower than that of MWNT-Arg. In vivo study revealed that Ag nanoparticle and MWNT-Arg decreased Hematocrit and mean number of red blood cells (RBC) statistically at concentration of 100 μg mL-1. The mean decrease of RBC and Hematocrit for Ag nanoparticles (18% for Hematocrit and 5.8 × 1,000,000/μL) was more than MWNT-Arg (20% for Hematocrit and 6 × 1000000/μL). In addition, MWNT-Arg and Ag nanoparticles had a direct influence on the White Blood Cell (WBC) drop. Regarding both nanostructures, although the number of WBC increased in initial concentration, it decreased significantly at the concentration of 100 μg mL-1. It is worth mentioning that the toxicity of Ag nanoparticle on WBC was higher than that of MWNT-Arg. Because of potent antimicrobial activity and relative hemocompatibility, MWNT-Arg could be considered as a new candidate for biomedical applications in the future especially for hemodialysis membranes.